MENGOPTIMALKAN PEMBELAJARAN DI ERA DIGITAL SEBAGAI UPAYA MENINGKATKAN KUALITAS PENDIDIKAN DI INDONESIA - Miftahul Huda; Faishol Hakim; Ahmad Zamakhsari; Nabil (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
Education in Indonesia faces significant challenges in improving its quality, especially in the rapidly evolving digital era. Information and communication technology offers opportunities to optimize the learning process, yet its implementation still encounters various obstacles. This research aims to identify ways to optimize learning in the digital era as an effort to enhance the quality of education in Indonesia. This study employs a qualitative approach, collecting data through in-depth interviews, observations, and document analysis. The subjects of the research include teachers, students, and education managers from several schools in Indonesia. The findings indicate that the use of digital technology in learning can enhance student motivation and engagement. Additionally, training for teachers in technology use is crucial for the successful implementation of digital learning. Digital learning has significant potential to improve the quality of education in Indonesia; however, challenges such as infrastructure and teacher training must be addressed. This research provides new insights into the integration of technology in education and offers practical recommendations for curriculum development and teacher training, which can help enhance the quality of education in Indonesia.